Densidad de siembra y comportamiento agronómico de tres variedades de maíz morado (Zea mayz L.) - Pedraza Guevara y Cols., Mario (2018)
The aim of this study was to evaluate the effect of three densities [40cmx60cm, 30cmx50cm and 20cmx60cm] on the agronomic behavior of three varieties of purple maize (Zea mayz L.) INIA-601, UNC-47 and PMV-581. Thus, soil sampling was carried out. The cultural work began with the preparation of the land, planting, handle of the crop and harvest. The project was located in the Quipachacha annex, Levanto district in the region of Amazonas at 2820 msnm, UNTRM Experimental Station, INDES - CES. The area of ​​land was 844.8m2 with dimensions of 13.20m wide by 64m long. The statistical design was factorial of 3 blocks (repetitions) and 09 demonstration plots (treatments), with separation of 1.0m between plots and 1.5m between blocks, furthermore, 1 control 60cmx40cm. The analysis of variance of the factors and study variables and their respective Tukey test in SPSS (Version 23.0) were used to test the hypothesis (p<0.05). The highest percentage of germination of 96.80 was found in the variety of UNC - 47 purple maize at planting density of 1.5 m2. At 93 days flowering was developed without significant difference between treatments. The variety INIA - 601 stood out at a higher plant height of 202.6cm (treatment 1) at 60cmx40 density. Moreover, 04 plants/linear m, 1.43 cob/plant at density 50cmx30 and greater weight of seeds 5,497 g. In the same way the variety PVM - 581 excelled with 145cm of insertion of corn that is to say to density of 60cmx20cm. The highest number of rows per ear was 11.83 and ear length 20.76cm at density of 60cmx40cm. The diameter > of cob was found in the variety PVM - 581 (4.93 cm) at density of 50cmx30cm. An average yield of purple maize of 4808.80 kg/ha was found in the variety INIA - 601 at density 60cmx40cm, consequently lower diameter of ear. The lowest yields were found in PVM - 581 at densities 2745.50 kg/ha.